2010
DOI: 10.1007/s10725-010-9459-8
|View full text |Cite
|
Sign up to set email alerts
|

Apoplasmic assimilates and grain growth of contrasting rice cultivars differing in grain dry mass and size

Abstract: Apical dominance in assimilate filling impacts grain growth in basal spikelets of rice panicle. In this study, organic materials of the pericarp, apoplasmic space and endosperm of the apical and basal caryopses, and photosynthesis of the flag leaf were measured during early part of grain development in three types of rice cultivars with similar phenology, but difference in grain weight and size in the dry and wet seasons of 2006 and 2007, respectively. Photosynthetic activity of the flag leaf was consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…At maturity, the control plant had higher carbohydrate content in the stem but lower in the grains (Figure 8) due to early senescence that reduced photosynthetic rate and leaf area compared to SPM treatment. Similar results were reported by Kuanar et al (2010), Ji et al (2012) and Sekhar et al (2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At maturity, the control plant had higher carbohydrate content in the stem but lower in the grains (Figure 8) due to early senescence that reduced photosynthetic rate and leaf area compared to SPM treatment. Similar results were reported by Kuanar et al (2010), Ji et al (2012) and Sekhar et al (2015).…”
Section: Discussionsupporting
confidence: 91%
“…Greater harvest index with SPM treatment indicated that rice plant managed to overcome the impact of water stress through improvement of photosynthesis and better assimilates distribution. In addition, results above also supported previous findings (Tang et al 2009;Kuanar et al 2010;Fu et al 2011) which showed that significant enhancement of the activities of starch biosynthesizing enzymes in rice panicles do influence the grain weight accumulations and also grain filling characteristics. The characteristic of grain filling depends on the supply of assimilates from source organs, as well as on the demand for assimilates within the embryonic tissues (sink activity), whereby both maternal and embryonic factors contribute to the maintenance of seed growth even under water stress (Lemoine et al 2013).…”
Section: Discussionsupporting
confidence: 89%
“…In the context of spikelet development in rice, the hormone balance becomes crucial for survival when a spikelet is disadvantaged because of its temporal or spatial location on the panicle axis. The inferior basal spikelets produced more ethylene than did the superior apical spikelets (Kuanar et al, 2010;Mohapatra and Mohapatra, 2005), and the high ethylene accelerated the senescence of the pericarp (Mohapatra and Mohapatra, 2006), retarded the development of male gametophytes (Naik and Mohapatra, 1999), diminished the activity of the starch-synthesizing enzymes, AGPase and sucrose synthase , increased chalkiness and decreased the quality of grains (Yang et al, 2007a), and reduced the rate of cell division and starch biosynthesis, resulting in the accumulation of unused sugars in the endosperm (Panda et al, 2009) during grain filling. However, the role of inhibitory hormones, such as ABA or ethylene, has not been studied as extensively as that of promoter hormones.…”
Section: Hormonal Regulation Of Spikelet Developmentmentioning
confidence: 89%
“…At the sink, unloading of sucrose depends on sink strength converting the material first into monosaccharides and later into starch. Kuanar et al (2010) measured the concentration of assimilates in the apoplasmic space of the developing rice caryopsis and found that it was positively correlated with endosperm cell number and grain weight. H þ ATPase hydrolyses ATP to drive the sucrose-H þ symporter (Taiz and Zeiger, 2002).…”
Section: Starch Biosynthesismentioning
confidence: 99%
“…Bread quality can be affected by grain genetics and by environmental factors such as soil conditions, irrigation, weather, seed storage conditions, and seed content (Noorka et al, 2009). Water deficits, high temperatures, and nutritional requirements during the post-anthesis and grain-filling stages have significant effects on many biochemical properties of wheat grains (Ashraf, 2010) and can directly affect leaf photosynthesis and the availability of assimilates (Kuanar et al, 2010;Zhang et al, 2010). Indeed, these factors can change the grain-filling rate and duration.…”
Section: Introductionmentioning
confidence: 99%